AN ACCOMMODATION STRATEGY IN EEMA A STRATEGIC BRIEF (Tufts Archival Research Center, 2007)
Report prepared for the tobacco industry outlining the threats the industry faces both politically in terms of the cost of cigarettes and the ability to smoke them in public and socially in terms of the social acceptability. Discusses efforts to address social acceptability including shifting the argument from health to individual rights and a “value alignment” between society and the tobacco industry.